2010
DOI: 10.1177/0193945910373754
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Nurses’ Professional Self-Concept, Health, and Lifestyles

Abstract: According to the American Nurses Association, the entire profession of nursing exists to serve and improve society's health. Thus, to become a nurse, individuals must master a body of knowledge surrounding numerous health aspects. While acquiring the unique knowledge, skills, and values of their profession, nurses form perceptions of personal adequacy in their role, known as professional or nurse self-concept. Given the centrality of health to the profession, it would seem logical that nurses would personally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 38 publications
3
47
1
2
Order By: Relevance
“…This is particularly important to the future of nursing as the profession has been called on the profession to lead change in advancing health policy (Institute of Medicine, 2011). Yet, this study found that leadership was the weakest aspect of the students' professional self-concept, mirroring findings from studies of practicing nurses (Cowin, 2001;Cowin, & Hengstberger-Sims, 2006;Hensel, 2011). If this is true perhaps the greatest challenge for the profession is not how to teach professional values, but how to recruit pre-licensure candidates who will best contribute to nursing's preferred future.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This is particularly important to the future of nursing as the profession has been called on the profession to lead change in advancing health policy (Institute of Medicine, 2011). Yet, this study found that leadership was the weakest aspect of the students' professional self-concept, mirroring findings from studies of practicing nurses (Cowin, 2001;Cowin, & Hengstberger-Sims, 2006;Hensel, 2011). If this is true perhaps the greatest challenge for the profession is not how to teach professional values, but how to recruit pre-licensure candidates who will best contribute to nursing's preferred future.…”
Section: Discussionsupporting
confidence: 63%
“…Healthy lifestyle practices are a major focus of nursing education, and nurses who live such lifestyles have also been found to have a stronger sense of professional adequacy (Hensel, 2011). One study found that efforts to improve self-care also improved student nurses' intent to provide care consistent with national quality and safety standards (Riley, & Yearwood, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…선행연구에서 영양지식이 높을수록 건강 에 좋은 음식을 섭취하고자 하는 경향이 높았고 [13] 현재까지 국외 간호대학생의 건강증진행위와 관련된 선행연구 로는 흡연 [17], 영양상태 [18], 간호교육 [19]에 관해 이루어지고 있고, 국내 간호대학생의 건강증진행위와 관련된 선행연구로는 지각된 건강상태 [6], 체질량지수 [20], 건강통제위 [21] …”
unclassified